Humor Therapy is Effective to Reduce Headache Related to Hypertension - Awaludin, Sidik; Purnawan, Iwan; Alivian, Galih Noor (Jurnal Keperawatan Soedirman, 2018)
Hypertension can lead to the heart disease, kidney, and stroke if the blood pressure is not controlled. Various complementary therapies are developed to reduce pain due to high blood pressure. Humor therapy can cause a relaxation response and reduce a headache. The purpose of this research was to identify the impact of humor therapy to reduce headache caused by hypertension. This research used a quasi-experimental design of pre and post control group design. The number of samples was 40 people with primary hypertension in Mersi village Purwokerto. The sampling technique used was purposive sampling. Numeric rating scale was applied to measure the pain scale. The difference of pain scale before and after the intervention was tested using Mann Whitney test. Statistical analysis result showed that humor therapy has a significant impact to reduce headache due to hypertension (p value = 0.000). Humor therapy is able to reduce headache due to hypertension significantly..